Condom Decision Making Among Latino and Black Adolescent Males: Social Neurobiological and Paternal Influences. (November 2021) - Guilamo-Ramos, Vincent; Benzekri, Adam; Thimm-Kaiser, Marco; Rivera, Margarita; Fuller, Taleria R.; Warner, Lee; Koumans, Emilia H. A.
Purpose: We explored mechanisms of paternal influence associated with adolescent male condom decision making and behavior within an integrated framework of social neurobiological and behavioral theories of condom use. Method: Self-administered surveys from Latino and Black adolescent males aged 15–19 years ( n = 191) and their fathers were obtained. Dyads were recruited using area sampling methodology. Analyses included multivariable logistic and ordinary least squares regression examining direct and indirect associations of adolescent decision-analytic and paternal influence factors with adolescent condomless sex in the past 3 months. Results: Notions of masculinity, low-risk perception, partner approval of, and self-efficacy for condomless sex were associated with engaging in unprotected sex. Adolescent males reported reduced odds of engaging in condomless sex when indicating greater levels of father–son communication, relationship satisfaction, and paternal monitoring. Conclusion: Father-based interventions grounded in integrated theoretical frameworks of behavioral decision making and neuroscience have the potential to promote condom use among adolescent males.